2021
DOI: 10.1155/2021/5567697
|View full text |Cite
|
Sign up to set email alerts
|

Acupoints for Tension-Type Headache: A Literature Study Based on Data Mining Technology

Abstract: Objectives. This study aimed to explore the characteristics and principles of acupoints, which were applied for treating tension-type headache (TTH). Methods. Four databases were searched for the literature studies of treating TTH with acupuncture and moxibustion up to September 1, 2020. Titles, journals, authors, key words, interventions, main acupoints, and outcomes of the included literature studies were extracted and inputted into the self-established Data Excavation Platform of Acupoint Specificity for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Systematic reviews and meta-analyses ( Deng and Wang, 2016 ; Kim et al, 2019 ; Li et al, 2020 ) indicated that the most frequently used acupuncture points for the treatment of MCI were Baihui (GV20), Fengchi (GB20), Shenting (GV24), and Sishencong (EX-HN1). Taiyang (EX-HN5), which can bring relaxation and refreshment as an acupressure point, is an ideal acupoint when treating disorders affecting the head ( Lu et al, 2021 ). Therefore, the following special acupoints were chosen in the present study: Baihui (GV20), Fengchi (GB20), Shenting (GV24), Sishencong (EX-HN1) and Taiyang (EX-HN5), as shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Systematic reviews and meta-analyses ( Deng and Wang, 2016 ; Kim et al, 2019 ; Li et al, 2020 ) indicated that the most frequently used acupuncture points for the treatment of MCI were Baihui (GV20), Fengchi (GB20), Shenting (GV24), and Sishencong (EX-HN1). Taiyang (EX-HN5), which can bring relaxation and refreshment as an acupressure point, is an ideal acupoint when treating disorders affecting the head ( Lu et al, 2021 ). Therefore, the following special acupoints were chosen in the present study: Baihui (GV20), Fengchi (GB20), Shenting (GV24), Sishencong (EX-HN1) and Taiyang (EX-HN5), as shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…It is mainly used to predict the likelihood of relationships among class members. For example, the probability of a given observation belonging to a specific category is judged by its related properties [14].…”
Section: Data Miningmentioning
confidence: 99%
“…Lu et al [3] said that the research of data mining technology has a history of many years, and many research institutes are often involved in data mining research; especially, more colleges have achieved remarkable achievements in this field [3]. Zhang [4] believed that data mining has also become a powerful tool for improving the quality of teaching and administration in colleges and universities.…”
Section: Literature Reviewmentioning
confidence: 99%